Still a New Problem for Defeasibility: A Rejoinder to Borges - WILLIAMS, John Nicholas (Institutional Knowledge at Singapore Management University, 2016)
I gave a new objection to the defeasibility theory of knowledge, namely that prohibits you from knowing that you know that p if your knowledge that p is a posteriori. Rodrigo Borges claims that Peter Klein has already satisfactorily replied to a version of my objection. He attempts to defend this reply and argues that my objection fails because a principle on which it is based is false. I show that my objection is not a version of the old one that Klein attempts (unsatisfactorily) to address, that Borges’s defence of Klein’s reply fails and that his argument against my new objection leaves it untouched.